"I want to leave, but there is nowhere to go": An examination of how reluctant stayers respond to abusive supervision. Issue 2 (18th November 2019) - Singh, Riann
Abstract : Purpose: Limited research has explored the behavioural tendencies of reluctant stayers. This study aims to expand research here to explain how employees who are victims of abusive supervision behave when they intend to leave but are unable to because of limited job alternatives. This study postulates that employees who are victims of abusive supervision are more likely to develop intentions to leave their job. Abusive supervision is expected to indirectly spur workplace deviance, with turnover intentions as the mediator. Further, the availability of job alternatives is expected to moderate the relationship between turnover intentions and workplace deviance, thereby forming a moderated-mediation model. Design/methodology/approach: Employee data were collected from 228 frontline employees within the banking sector of Trinidad, using a two-wave research design. A path-analytic approach was used to test the research relationships. Findings: The findings provided support for the propositions that abusive supervision predicts turnover intentions, that turnover intentions mediate the abusive supervision – workplace deviance relationship, and that the availability of job alternatives moderate the relationship between turnover intentions and workplace deviance. Originality/value: This study addresses a clear research gap, as no study has examined how employees who are victims of abusive supervision behave when they intend to leave but are unable to because of limited job alternatives. In fact, few studies have explored the behaviour of reluctant stayers and the moderating role of job alternatives in the behaviours of such stayers.